Mandarese Phonological Inter-Language Of English Teachers - Nurliah, Nurliah; Jubhari, Yuriatson; Amaliah, Nurul; Sasabone, Luana (Jurnal Scientia, 2024)
The Mandarese sounds interfered the English sounds. This research aimed to describe the kinds of the Mandarese sounds that substituted the English sounds in a word and to find out where position in a word of the Mandarese sounds substituted the English sounds.The method used in this research was the descriptive qualitative and quantitative method. Qualitative applied to describe where the position of Mandarese sounds substitute the English sounds in a word. The quantitative method was applied to count how many times the Mandarese sounds substituted the English sounds. This research carried out in Polman regency. The primary data were gathered from 30 English teachers through (1) observation, when they were teaching in their classes. It aimed to compare the producing of sounds when they read and not. (2) By asking the teachers to read the reading text. The result shows that the Mandarese sounds interfered the English sound in a word. It was proven by the percentage of appearances of the Mandarese sounds, 47%, and the English sound, 32 %. And substitution happened in initial, middle, and final positions for the English sounds such as [æ], [ə],[e], [I], [v], [f], [ò], [z], [ð] by [ε], [i:], [p], [s], [d], [t].